Enhancing patient flow through standardised discharge pathways for neurology and medicine services - Marc R Nuwer; Colin M McCrimmon; Molly R Fensterwald; Linda K Czypinski; Sherrille E Abelon; Melissa Reider-Demer (BMJ Open Quality)
Background and objectives Poor discharge planning impairs hospital throughput, adds to the financial strain on health systems and diminishes patient and provider satisfaction. We developed consensus-based discharge criteria coupled with a standardised discharge pathway for four presenting diagnoses and tracked their effect on discharge timing and length of stay (LOS).Methods Medical readiness for discharge criteria for patients diagnosed with transient ischaemic attack, seizure, demyelinating disease or syncope were generated by expert consensus at our institution. A standardised discharge pathway was developed for eligible patients based on discussions with stakeholders and staff. Discharge timing and readmissions were tracked for 6 months pre-intervention and 12 months post-intervention (divided into 6 months of implementation and post-implementation periods). The primary outcome was a discharge time of ≤2 hours for 60% of patients during the implementation period. Secondary outcomes included reduced time to discharge (TTD) and LOS compared with the pre-intervention period.Results 318 total patient visits were included across the baseline, implementation and post-implementation periods. Median TTD improved from 171 min at baseline to 88 and 92 min, respectively, during the implementation and post-implementation periods. Median LOS similarly decreased from 94 hours to 35 and 30 hours, respectively. All primary and secondary outcomes were achieved during the implementation period and sustained post-implementation. The rate of emergency department visits and hospital readmissions within 30 days remained low (~1.5%) post-intervention. Additionally, most providers reported that the intervention improved clinical workflow.Conclusions This standardised discharge framework improved discharge efficiency for patients with four common diagnoses during an 18-month quality improvement study. The framework and its implementation are highly scalable, and similar systems-level approaches should be considered by hospitals to improve throughput.